Fathers' Involvement with Their Nonresident Children and Material Hardship - Nepomnyaschy, Lenna (2011)
Children in single-parent families, particularly children born to unmarried parents, are at high risk for experiencing material hardship. Previous research based on cross-sectional data suggests that father involvement, especially visitation, diminishes hardship. This article uses longitudinal data to examine the associations between nonresident fathers' involvement with their children and material hardship in the children's households. Results suggest that fathers' formal and informal child support payments and contact with their children independently reduce the number of hardships in the mothers' households; however, only the impact of fathers' contact with children is robust in models that include lagged dependent variables or individual fixed effects. Furthermore, cross-lagged models suggest that material hardship decreases future father involvement, but future hardship is not diminished by father involvement (except in-kind contributions). These results point to the complexity of these associations and to the need for future research to focus on heterogeneity of effects within the population.